Ceratozetes spitsbergensis Thor 1934 - Behan-Pelletier, Valerie M.; Lindo, Zoë (Zenodo, 2019)
Ceratozetes spitsbergensis Thor, 1934 Geographic Location and Habitats : AK, Brooks Range, moss and lichens in alpine tundra (Behan- Pelletier 1985); YT : Richardson Mtns (Behan-Pelletier 1997b). Distribution : Holarctic. : Published as part of Behan-Pelletier, Valerie M. & Lindo, Zoë, 2019, Checklist of oribatid mites (Acari: Oribatida) of Canada and Alaska, pp. 1-180 in Zootaxa 4666 (1) on page 133, DOI: 10.11646/zootaxa.4666.1.1, http://zenodo.org/record/4000595 : {"references": ["Thor, S. (1934) Neue Beitrage zur Kenntnis der Invertebraten Fauna von Svalbard. Zoologischer Anzeiger, 107, 114 - 139.", "Behan-Pelletier V. M. (1997 b) Oribatid mites (Acari: Oribatida) of the Yukon. In: Danks, H. V. & Downes, J. A. (Eds.), Insects of the Yukon. Biological Survey of Canada (Terrestrial Arthropods), Ottawa, pp. 115 - 149."]}